Pneumonia in Broiler Chicken Flocks Associated with β-Hemolytic Ornithobacterium rhinotracheale Infection - Churria, Carlos D. Gornatti; Sansalone, Pablo L.; Vigo, Germán B.; Sguazza, Guillermo H.; Machuca, Mariana A.; Origlia, Javier A.; Píscopo, Miguel V.; Loyola, Miguel A. Herrero; Petruccelli, Miguel A. (Brazilian Journal of Veterinary Pathology, 2011)
Broiler chickens aged 40 and 46-days-old from two neighboring flocks belonging to a commercial broiler complex, presenting facial edema, severe respiratory signs and 10% mortality were analyzed. Pneumonic lesions and opaque thoracic and abdominal air sacs with foamy exudate were seen at postmortem examination. Histopathology of lungs showed fibrinoheterophilic pneumonia in both cases. Small pin point colonies with extensive β-hemolytic activity were isolated from tracheal and lung tissue samples and identified as Ornithobacterium rhinotracheale by polymerase chain reaction (PCR). Results of lung histopathology, bacteriological isolation and PCR identification confirmed the diagnosis of pneumonia caused by β-hemolytic O. rhinotracheale infection in both broiler chicken flocks. This paper appears to be the first report of β-hemolytic O. rhinotracheale field isolates obtained from broiler chickens associated with severe respiratory signs and pneumonia.